Systematic Literature Review on Digital Technology in Primary School Learning (2020–2025) - Atik Prihatini; Deni Setiawan; Decky Avrilianda; Ellianawati Ellianawati (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
The rapid development of digital technology has transformed learning practices in primary education. This study aims to examine the effectiveness of digital learning and identify key challenges in its implementation at the primary school level. Using a Systematic Literature Review (SLR) approach, ten empirical studies published between 2020 and 2025 were systematically selected and reviewed following the PRISMA protocol. The findings show that digital-based learning improves students' academic outcomes by an average of 24.2% and enhances learning engagement, particularly when interactive media and digital platforms are integrated into instruction. However, several challenges persist, including limited device availability, inadequate digital infrastructure, and low teacher readiness in adopting technology-supported pedagogy. These barriers particularly affect schools in underserved areas and hinder the equitable implementation of digital learning. The study concludes that digital technology has strong potential to enhance learning effectiveness but requires strategic and context-sensitive integration. The implications highlight the need for blended learning–based curricula, equitable technological access, and continuous teacher professional development to support sustainable and inclusive digital learning in primary schools.